Extending Pervasive Devices with the Semantic Grid: A Service Infrastructure Approach. - Guan, T; Zaluska, E; Roure, D (IEEE, 2006)
Pervasive computing devices are gradually becoming increasingly prevalent in our everyday life, enabling the users in the physical world to interact with the digital world. Grid computing provides a vision of accessing computational resources automatically on demand to deliver the services required with the appropriate quality. Semantic Web technologies enable automation and interoperability. It is the interaction of Semantic Grid and the physical world (pervasive devices) that will enable us to a new concept of "ambient intelligence", the notion of intelligence in the surrounding environment supporting the activities and interactions of the users. This paper presents a service approach that extends pervasive devices with semantic Grid services by using a device-proxy-Grid system infrastructure. OWL-S is used to describe different proxy devices' capability in order to realize automatic proxy service discovery. A context model is also discussed to enhance the intelligence of the system. © 2006 IEEE.